ANALISIS DIMENSIONALITAS DATA MAGNETOTELURIK LAPANGAN PANAS BUMI â€œSAâ€ BERDASARKAN METODE TENSOR FASE - Akbar, Shofya; Setyawan, Agus; Yulianto, Tony; Baroek, Marino Christiano; Ramadhan, Irvan (BERKALA FISIKA, 2020)
Magnetotelluric (MT) method is one of a passive electromagnetic method in geophysics. Principally MT measures the temporal variation of the electromagnetic field that is induced to the surface of the earth to get the subsurface resistivity structure. Information about the geoelectric strike and dimensionality of the magnetotelluric data is important to modelling the subsurface structure. Information is used to determine the 1D, 2D or 3D approach that can be used to interpret MT data. Therefore, an aim of study is to identify the direction of the geoelectric strike and dimensionality structure in the